The future of reorganization procedures in the era of pre-insolvency law - Aurelio GURREA-MARTINEZ (Institutional Knowledge at Singapore Management University, 2019)
Several countries and regions around the world, including Singapore, the United Kingdom, and the European Union are amending their restructuring framework to implement a pre-insolvency mechanism that looks like a US Chapter 11 reorganization. However, unlike what happens in the United States, where unsuccessful reorganizations lead to Chapter 7 liquidations, companies using this ‘de facto Chapter 11’ (DFCH11) are still allowed to use the formal reorganization procedures existing in their insolvency jurisdictions if the DFCH11 fails.